In situ transesterification of solid coconut waste in a packed bed reactor with polyvinyl alcohol (PVA) - supported calcium oxide catalyst - Nur Syakirah binti Talha (Kulliyyah of Engineering, International Islamic Universiti Malaysia, 2017)
Conventionally, biodiesel is produced by transesterification of vegetable oils or animal fats using homogeneous basic catalyst. However, conventional method is high in cost as a lot of hexane is used for oil extraction and more complex separation process needed to separate catalyst from product. In situ transesterification method is a simplified method for biodiesel production where the oil was simultaneously extracted and transesterified into alkyl ester in-situ in one single process using alcohol in the presence of catalyst. This process combines the steps of lipid (oil) extraction and transesterification. Methanol was used as it is widely available and economically feasible. In this study, in situ transesterification was conducted using solid coconut waste and a waste-derived heterogeneous catalyst synthesized from eggshells and solid coconut waste by calcination. Reaction temperature, catalyst loading, and methanol to solid ratio were varied from 55 to 65˚C, 0.5 to 5.5 wt %, and 8:1 to 12:1, respectively. Meanwhile, reaction time was fixed to 3 hrs. Packed bed system was used in the production of biodiesel since it produced higher yield and has easier separation of product as compared to batch flask. Heterogeneous catalyst can help to reduce the steps in separation and purification of the product. Moreover, utilizing waste in the production can lower the production cost as well as help to save and clean the environment. The highest biodiesel yield using batch flask of 85.10% was observed at the optimized temperature of 62˚C, catalyst loading of 5.5 wt %, and methanol to solid ratio of 12:1. Whilst packed bed system obtained highest biodiesel yield of 94.55% at the optimized temperature of 61˚C, with catalyst loading of 2.29 wt%, and methanol to solid ratio of 12:1. The study of the kinetic of in situ transesterification of solid coconut waste using first order kinetic model was attested by Thiele modulus less than 2. The activation energy observed for the reaction was 115.49 kJ/mol.